2008
DOI: 10.1007/s00418-008-0412-0
|View full text |Cite
|
Sign up to set email alerts
|

The art of cellular communication: tunneling nanotubes bridge the divide

Abstract: The ability of cells to receive, process, and respond to information is essential for a variety of biological processes. This is true for the simplest single cell entity as it is for the highly specialized cells of multicellular organisms. In the latter, most cells do not exist as independent units, but are organized into specialized tissues. Within these functional assemblies, cells communicate with each other in diVerent ways to coordinate physiological processes. Recently, a new type of cell-to-cell communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
193
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(195 citation statements)
references
References 65 publications
2
193
0
Order By: Relevance
“…They were identified in a variety of cultured cell systems, including cells of the immune system, kidney cells, PC12 cells and cells from human glioblastoma (figure 4 and table 2) [13,32,33,101,102]. TNTs have a diameter of 50-200 nm and a length up to several cell diameters.…”
Section: Tunnelling-nanotube Type Of Wiring Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were identified in a variety of cultured cell systems, including cells of the immune system, kidney cells, PC12 cells and cells from human glioblastoma (figure 4 and table 2) [13,32,33,101,102]. TNTs have a diameter of 50-200 nm and a length up to several cell diameters.…”
Section: Tunnelling-nanotube Type Of Wiring Transmissionmentioning
confidence: 99%
“…Cargo transfer of endosome-derived vesicles and membrane-anchored proteins takes place. The mechanism involves a unidirectional vesicle transfer which is based on actin action [101]. It seems possible that membrane receptors can move via TNTs from the plasma membrane of one cell to the plasma membrane of another cell [53].…”
Section: Tunnelling-nanotube Type Of Wiring Transmissionmentioning
confidence: 99%
“…The connecting structures, called nanotubes, can bridge distances of more than 100 μm, depending on the cell type [48,49]. They are versatile in ultra-structure and formation, and consequently also in function [reviewed in [50][51][52][53]. Our recent results revealed that the nanotubes in epithelial cells can be divided into two distinct types with respect to their formation, stability and cytoskeletal content [9].…”
Section: Membrane Nanotubesmentioning
confidence: 99%
“…Intercellular nanotubes (ICNs) formed from filopodial structures or after separation of tight cell-cell contacts mediate transport processes between cells. For example, diffusion of inositol triphosphate through nanotubes possibly mediates calcium signaling between macrophages, a gradient of membrane tension can induce transport of membrane patches and surface proteins, and molecular motors can transport organelles along filamentous actin in ICNs [5][6][7] . Land plants have developed plasmodesmata, a form of sophisticated membrane channel used to span the rigid cell walls to mediate the cell-to-cell exchange of signaling molecules 8 .…”
Section: Introductionmentioning
confidence: 99%